2019
DOI: 10.1111/1751-7915.13464
|View full text |Cite
|
Sign up to set email alerts
|

Viral composition and context in metagenomes from biofilm and suspended growth municipal wastewater treatment plants

Abstract: Summary Wastewater treatment plants (WWTPs) contain high density and diversity of viruses which can significantly impact microbial communities in aquatic systems. While previous studies have investigated viruses in WWTP samples that have been specifically concentrated for viruses and filtered to exclude bacteria, little is known about viral communities associated with bacterial communities throughout wastewater treatment systems. Additionally, differences in viral composition between attached and suspended gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 48 publications
9
24
0
Order By: Relevance
“…The immense number of viruses and viral particles that populate marine environments have a tremendous effect on microbial diversity directly (e.g., selectively killing of microorganisms) and indirectly (e.g., genetic material cycling, horizontal gene transfer) (Suttle, 2007;Cai et al, 2019). Of note, the high virus abundance in ecosystems such as a wastewater treatment plant may also play a role in the acquisition of mobile genetic elements in the genome of Dhc strain 195 (Seshadri et al, 2005;Petrovich et al, 2019). Therefore, experimental evidence and in silico analyses are still required to unravel the mechanisms leading to comparatively more horizontally transferred genes in the Dia marine genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The immense number of viruses and viral particles that populate marine environments have a tremendous effect on microbial diversity directly (e.g., selectively killing of microorganisms) and indirectly (e.g., genetic material cycling, horizontal gene transfer) (Suttle, 2007;Cai et al, 2019). Of note, the high virus abundance in ecosystems such as a wastewater treatment plant may also play a role in the acquisition of mobile genetic elements in the genome of Dhc strain 195 (Seshadri et al, 2005;Petrovich et al, 2019). Therefore, experimental evidence and in silico analyses are still required to unravel the mechanisms leading to comparatively more horizontally transferred genes in the Dia marine genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments laid out in this study identified 26 phage-host interactions in a hospital wastewater virome. Most of these were predictions of phages adsorbing to Proteobacteria, which is consistent with recent findings that these bacteria are ubiquitous and abundant in global waste water communities 277,278 . Several of the putative adsorbing viral populations represented rare members of the sampled hospital wastewater virome.…”
Section: Resultssupporting
confidence: 90%
“…Notably, 22 of the 26 selected viral populations putatively adsorb to Proteobacteria cell envelopes, consistent with recent findings that Proteobacteria are the dominant bacterial phylum in global wastewater treatment plant microbiomes and are abundant in wastewater influent 277,278 . It is thus likely that Proteobacteria phages are common in wastewater microbiomes, which supports our findings.…”
Section: Selection Of Phages With Putative Adsorption Activitysupporting
confidence: 86%
“…Wastewater treatment plants (WWTPs), in general, have high density and diversity of viruses [72] . Human enteric viruses studied (rotavirus and enterovirus) in the final effluents of five WWTPs showed the persistence of Rotavirus (up to 10 5 genome copies (GC)/L in 41.7% of the samples) [73] .…”
Section: Occurrence Of Virus In Environmental Matrixmentioning
confidence: 99%
“…Avian influenza virus (H6N2) survived in methanogenic landfill leachates and water showed rapid inactivation at elevated temperature and non-neutral pH while conductivity did not show any influence on the survival [76] . Viruses abundance in wastewater streams also influenced the bacterial community structure and catalyzed virus-mediated horizontal gene transfer [72] . Bacteriophages associated with the human GI tract are commonly reported in wastewater and phages infecting Bacteroides are used as an indicator for assessing the wastewater quality and contamination [77] .…”
Section: Occurrence Of Virus In Environmental Matrixmentioning
confidence: 99%